The Effect of Fresh Cow Milk and Dextrin Concentration on Quality of Instant Chocolate Drink - Mellyana Nurhidayah; Sentosa Ginting; Zulkifli Lubis (Universitas Sumatera Utara, 2014)
This research was conducted to find the effect of fresh cow milk and dextrin concentration on quality instant chocolate drink. This research had been perform using factorial completely randomized design with 2 factors, i.e. fresh cow milk concentration (S): 15%, 25%, 35% and 45% and dextrin concentration (D) : 4%, 6%, 8% and 10%. Parameters analyzed were moisture content, solubility, fat content, protein content, orgnoleptic value of colour, flavor and taste.This research showed that freshcow milk concentration had highly significant effect on moisture content, solubility, fat content, protein content, organoleptic of value, flavor and taste. Dextrin concentration also had highly significant effect on moisture content, solubility, organoleptic value of colour, flavor and taste, and had significant effect on fat content and protein content. Fresh cow milk concentration of 45% and dextrin concentration of 8% produced best quality of instant chocolate drink. Keywords: Instant Chocolate Drink, Fresh Cow Milk Concentration,Dextrin Concentration.